Umbilical cord mesenchymal stem cell exosomal miR-143-3p delays endothelial cell senescence through targeting COX-2 - Zhi-peng Yang; Shui-hong Lu; Yan-hong Pan; Zhao-fu Liao; Yi-tuan Xie; Heng Li; Yu-lan Zhou; Zhen-can Shi; Yun-fei Qu; Zhu-guo Wu; Chongxiang Xiong; Xing-dong Xiong (PLoS ONE, 2025)
Senescence of vascular endothelial cells leads to endothelial dysfunction and exacerbates atherosclerosis. In this study, we presented evidence that exosomes derived from human umbilical cord mesenchymal stem cells (hucMSC-Exos) could delay endothelial cell senescence, promote endothelial cell proliferation, and enhance angiogenic activity in vitro. The miRNA profiling analysis revealed a high expression of miR-143-3p in hucMSC-Exos, which was further upregulated in endothelial cells treated with hucMSC-Exos. Silencing miR-143-3p induced endothelial cell senescence, as evidenced by increased senescence-associated β-galactosidase activity, reduced cell proliferation, and inhibited tubular formation; conversely, overexpression of miR-143-3p exhibited opposite effects. Moreover, we found that miR-143-3p directly targeted Cyclooxygenase-2 (COX-2) and suppressed its translation, thus delaying endothelial cell senescence. These results suggested that hucMSC-Exos can delay endothelial cell senescence by transferring miR-143-3p. In summary, our data demonstrated the potential of hucMSC-Exos as an intervention against vascular aging.